"You Get More Than You Give": Experiences of Community Partners in Facilitating Active Recreation with Individuals who have Complex Communication Needs. (2nd April 2016) - Hajjar, David J.; McCarthy, John W.; Benigno, Joann P.; Chabot, Jennifer
Abstract: Recreation is an essential part of life that provides enriching experiences that may define one's life course similar to careers or other interests. An understanding of the role of volunteers in active community-based recreational programs can help to generate ways to enhance participation and contribute to additional communication opportunities with people who have complex communication needs. Nine volunteers from two adaptive ski programs and one therapeutic horseback-riding program in the Northeast region of the United States participated in semi-structured interviews. Audio-recordings were transcribed and analyzed and resulted in five thematic areas: (a) benefits, (b) why individuals volunteer, (c) barriers, (d) successful program supports, and (e) who are the riders and skiers using AAC. The findings provided insight to support the notion that active community-based recreational activities foster an environment for communication, meaningful engagement, and social relationships between volunteers and people with complex communication needs.